Raman Spectroscopy in Optical Non-Invasive Diagnostics of Skin Neoplasms - O. I. Kaganov; I. G. Loginova; A. A. Moryatov; S. V. Kozlov; A. E. Orlov; I. A. Bratchenko; B. B. Dzhuraev (Креативная хирургия и онкология, 2024)
Introduction. Recent decades indicate a significant increase in the incidence of skin cancer. Aim. To upgrade the specialized device and to improve the quality of skin neoplasm diagnostics. Materials and methods. The study mainly involved the method of non-invasive differential diagnostics of skin neoplasms. The method relies upon optical research methods, including Raman spectroscopy, a spectroscopic technique. A 10-year study, conducted by the Department of Oncology, the Samara Regional Clinical Oncology Dispensary (SOKOD), included more than 500 observations. The study used samples of various skin neoplasms obtained during surgical treatment of patients. Experimental tests provided a certain spectrum of various benign and malignant human skin neoplasms, including melanoma. Results. A series of experimental tests resulted in an experimental setup that is absolutely safe to use. Discussion. The study involved comparison of individual characteristics of the Raman spectra, obtained in the examination of neoplasm and healthy skin for each patient, thereby individualizing the method. The study revealed a high accuracy rate of 92% (with sensitivity of 89%, specificity of 93%), thus minimizing risks of false negative results, which is essential for mass examination. Conclusion. Since the proposed device setup does not require consumable products and different reagents, the method is marked with lower time costs and maintenance burden. Raman spectroscopy obtains a significant potential, thus, can be widely used for skin neoplasms in various medical and preventive institutions.